Evaluation of coolant concentration on the machiniability of carbon steel during end milling - Thangavelu, T. R. Anbarasan (2007)
In machining, cutting tools are used to remove unwanted material from the surface of a workpiece. This operation will transform the mechanical energy into thermal energy, generating heat at a small location. The generated heat transferred into the workpiece, the removed material, the environment and also the tool. This directly affects the tool life, the cutting performance and the quality of the products especially the surface finish. The cutting fluid is used to act as the coolant to reduce the generated heat and as lubricant to reduce the friction during the cutting process. This study explores the influence of coolant concentration on tool life, surface roughness of the product and the cutting force during end milling of mild steel S50C. High Speed Steel end mill of 4 flutes was used at various cutting conditions in the investigation. A design of experiment was planned, whereby the coolant concentration with cutting speed and feed being the factors and tool life, surface roughness and cutting forces were treated as responses. Mathematical models on the above responses were established based on the experimental results. The results of this experiment show that coolant concentration significantly affects the tool life at certain milling condition especially lower cutting speed and lower feed. At higher feed or cutting speed conditions, the coolant concentration or the coolant itself does not have any impact on the tool life. Coolant concentration does not directly affects the surface roughness but its’ reaction with feed does influence the results. The influence of coolant concentration on cutting force is not significant in this experimentation.